Protection of reproductive health: international and national experience - I.M. Zharovska; M.M. Blikhar; R.M. Matkivska; L.A. Cherkasova (Publishing House TRILIST, 2022)
Objectives: consideration at the scientific level of the problem of the nation's reproductive health protection in the context of international regulation and individual national experience. Materials and methods. The statistical method and the author's survey method were used for the collection and effective processing of public information. 200 women and 100 men aged 21 to 45 were selected as respondents. It was used a direct interview with respondents. The survey was conducted in Kyiv, Lviv, and Volyn regions in 2020-2022. International monitoring reports, global and national statistics, doctrinal developments of scientists of foreign countries (among them Great Britain, China, USA) were also used. Results. The main causes of impaired human reproductive health are: environmental, socio-economic (unresolved issues of abortion and proper contraception, violence against women and children) and medical problems. In Ukraine, neither specialized legislative acts nor bylaws contain a comprehensive strategy for the protection of reproductive health, which causes gaps in the legal regulation and social security of this area. Gender discrimination is a widespread phenomenon in our country. We must state the discriminatory situations and oppression of both sexes in the reproductive sphere. There are no systematic mechanisms for the prevention of this problem, and the attention of state legal, scientific and public institutions to this problem is insufficient. Conclusions. Legal policy in the field of reproductive health needs a complementary approach and renewal of strategic understanding at the level of the state legal policy. Only comprehensive consideration of reproductive health problems in Ukraine can ensure their solution. Reproductive counseling should be proactive and encouraged because its implementation is beneficial for the patient's mental health, quality of life, and adherence to treatment. Providing reproductive health education improves knowledge, attitudes and practices in the field of human reproduction.